On the finite images of finitely generated perfect groups - Nikolov, N (2023)
Let d≥2 be an integer. We conjecture that there is a finitely generated perfect group whose homomorphic images include all finite d-generated perfect groups. We prove a special case of this conjecture for the finite perfect groups with a subnormal series of bounded length and factors which are abelian or semisimple.